2013
DOI: 10.4102/rw.v4i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive awareness of reading strategies of University of Botswana English as Second Language students of different academic reading proficiencies

Abstract: This study explored metacognitive awareness level of University of Botswana students in the Faculty of Social Sciences. It also considered the more recent research focusing on the role of metacognitive awareness in reading and how it relates to proficiency. The following questions are addressed: (1) What are the self-reported reading proficiencies of the University of Botswana students? (2) Are the University of Botswana students aware of their metacognitive reading strategies? (3) What kind of metacognitive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 10 publications
7
20
2
3
Order By: Relevance
“…proved that they are high users of the overall strategies (M=3.6023, S.D.=1.3189). This outcome supports previous studies like Jom'a (2013), Chen and Chen (2015), Mahasneh, Alkhawaldeh and Almakanin (2016), Monsakorn (2012), Zarrabi (2015), Rastegar, Kirmani and Khabir (2017), Poole (2009), Magogwe (2013 and Lien (2014) Who regardless of the aims of their studies have found their participants to be high users of the overall metacognitive reading strategies. The results of the present study are not consistent with other studies like Tabtabaei and Assari (2011), Jafari and Shokrpour (2012), Shikano (2013), Lee (2012), Tavakoli (2014), Hoang (2016 who conducted studies for a variety of aims found their participants to be moderate users of the overall reading strategies.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…proved that they are high users of the overall strategies (M=3.6023, S.D.=1.3189). This outcome supports previous studies like Jom'a (2013), Chen and Chen (2015), Mahasneh, Alkhawaldeh and Almakanin (2016), Monsakorn (2012), Zarrabi (2015), Rastegar, Kirmani and Khabir (2017), Poole (2009), Magogwe (2013 and Lien (2014) Who regardless of the aims of their studies have found their participants to be high users of the overall metacognitive reading strategies. The results of the present study are not consistent with other studies like Tabtabaei and Assari (2011), Jafari and Shokrpour (2012), Shikano (2013), Lee (2012), Tavakoli (2014), Hoang (2016 who conducted studies for a variety of aims found their participants to be moderate users of the overall reading strategies.…”
Section: Discussionsupporting
confidence: 79%
“…Jafari andShokrpour (2012), Jom'a (2013), Magogwe (2013), Shikano (2013) and Mahasneh, Alkhawaldeh and Almakanin (2016). Studies that do not support these findings do also exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also supports the findings of Hong-Nam and Page (2014) on the moderate use of metacognitive reading strategies of ELLs in America. However, this particular result of the study does not coincide with the general findings of previous researches showing active (High) overall use of metacognitive reading strategies by EFL students in Yemen (Al-Sobhani, 2013) and by those ESL students in Malaysia (Pammu, Amir, & Maasum, 2014;Maasum & Maarof, 2012) and in Botswana (Magogwe, 2013). This finding suggests that use of metacognitive strategies vary depending on language learners' settings and orientations.…”
Section: Discussioncontrasting
confidence: 56%
“…Awareness and use of metacognitive reading strategies have positive and direct relationship with reading comprehension performance; thus, students who use these strategies perform better in reading proficiency tests / courses (Yuksel & Yuksel, 2012;Pressley, et al, 1998;Al-Sobhani, 2013;Tavakoli;Magogwe, 2013;Hong-Nam, 2014;Zhang & Seepho, 2013;Memis & Bozkurt, 2013;Phakiti, 2006;Kummin & Rahman, 2010). Therefore, learning metacognitive reading strategy skills can be one solution to the problem of poor reading comprehension, hence, the need for it to be developed and emphasized in the EFL teaching and learning processes.…”
Section: Metacognitive Reading Strategiesmentioning
confidence: 99%